Mosquito Repellent Potential of Carpesium abrotanoides Essential Oil and Its Main Components Against a Dengue Vector, Aedes aegypti (Diptera: Culicidae). Issue 3 (14th February 2022) - Haris, Abdullah; Azeem, Muhammad; Binyameen, Muhammad
Abstract: Disease vectoring mosquitoes are a serious threat to humans. However, till today only few mosquito repellents have been identified. The current study was conducted to evaluate the repellent potential of Carpesium abrotanoides essential oil against Aedes aegypti females by human bait technique. Essential oil was extracted by steam distillation process while the identification of chemical constituents was carried out by gas chromatography–mass spectrometry. Time span repellent bioassays of C. abrotanoides essential oil in comparison to DEET were performed at three different doses (33 μg/cm 2, 165 μg/cm 2, and 330 μg/cm 2 ) under laboratory conditions. Highest repellency periods for essential oil and DEET were observed at the tested dose of 330 μg/cm 2 with 315 min and 720 min, respectively. Lowest repellency period of 45 min for essential oil and 105 min for DEET was recorded at the tested dose of 33 μg/cm 2 . Major constituents caryophyllene (24.3%) and trans -nerolidol (12.0%) of C. abrotanoides essential oil were also evaluated as repellents at three different doses (330 μg/cm 2, 165 μg/cm 2, and 33 μg/cm 2 ) against Ae. aegypti . Surprisingly, trans -nerolidol completely inhibited Ae. aegypti landings for 45 min when tested at 330 μg/cm 2 . However, caryophyllene did not completely inhibit Ae . aegypti landing even after immediate application at the tested dose of 330 μg/cm 2 . At the tested dose of 330 μg/cm 2, the mixture ( trans- nerolidol + caryophyllene) completely inhibited Ae. aegypti landing for 60 min indicating the synergistic effect of caryophyllene. Hence, C. abrotanoides as well as its major constituent, especially trans -nerolidol, have potential to formulate as mosquito repellent comparable of DEET.